PEDIATRIC NURSES' ATTITUDES REGARDING MALPRACTICE TENDENCIES AND PATIENT SAFETY CULTURE: A CASE OF TURKEY - Esra Tural Büyük (Rojan GÜMÜŞ, 2021)
Background: Pediatric nurses provide care to children, which is why they play an essential role in preventing medical errors and ensuring patient safety. Objectives: This comparative and descriptive study was conducted to determine the attitudes of pediatric nurses in Turkey regarding malpractice tendencies and patient safety culture and to reveal the relationship between them. Material and Methods: The study was conducted in the pediatric clinics of a university hospital and a public hospital in a metropolis in the northern region of Turkey. The study population included 142 nurses. A 'Nurse Information Form', a 'Patient Safety Culture Scale (PSCS)', and a 'Malpractice Tendency Scale in Nursing (MTSN)' were used to collect information. Data were analyzed by using SPSS 16 program, descriptive statistics, Independent Two-Sample t-test, one-way analysis of variance (ANOVA), Tukey test, Tamhane test, Mann Whitney U, Kruskal Wallis test and Pearson correlation tests. Results: Nurses who had a master's degree, made a medical error, and observed medical errors made by another colleague had a higher mean MTSN score (p<0.05). Nurses aged 46 and older, with a master's degree, that worked in the pediatric unit as a manager had a higher total mean PSCS score (p<0.05). A positive and significant relationship was found between total mean PSCS and MTSN scores. Conclusions: This study found that pediatric nurses' level of malpractice tended to be low and their level of patient safety culture perceptions high, which is significant in terms of quality of patient care.